Adjustment and integration in small emerging economies (a Caribbean Community agenda) : (final report) - Clarke, Laurence ed. (CCMS St. AugustineTT, 1998)
Focuses on the characteristics and recent economic trends of the CARICOM region, surveys the literature on the problem of 'size' and the experience of small states in adjustment and integration in recent years, and adumbrates some of the related challenges ahead for CARICOM states. Examines the adjustment experience of small states and the implications for CARICOM. Examines the adjustment experience of small states and the implications for CARICOM. Discusses the special role of the private sector. Emphases the challenges the CARICOM region will continue to face at the conclusion of the decade of the 1990s and beyond.